A high-strength and tough three-phase eutectic high-entropy alloy and preparation method thereof

By adjusting the composition ratio and smelting method of CoCrFeNi:NiAl:Nb, the FCC + Laves + NiAl three-phase eutectic high-entropy alloy is formed, the problem of poor strength of CoCrFeNi alloy is solved, high-strength plasticity and multi-scale structure are achieved, and the Comprehensive properties of alloys.

CN116356187BActive Publication Date: 2024-12-20CHINA THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310258326.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2024-12-20
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

CoCrFeNi-based high-entropy alloys have good plasticity but poor strength, making it difficult to improve their overall performance.

Method used

By adjusting the composition ratio of CoCrFeNi:NiAl:Nb and using specific smelting methods and raw material laying order, FCC + Laves + NiAl three-phase eutectic high-entropy alloy is formed to improve the microstructure and mechanical properties of the alloy.

Benefits of technology

The high-strength plastic matching of the alloy is achieved, and a multi-scale multi-stage structure is formed, which enhances the mechanical properties of the alloy, reduces the current demand and the evaporation of aluminum elements, and ensures the uniformity of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116356187B_ABST
    Figure CN116356187B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-strength and toughness three-phase eutectic high-entropy alloy and a preparation method thereof. The atomic components of the three-phase eutectic high-entropy alloy are Co, Cr, Fe, Ni, Nb and Al, wherein the atomic percentages of the three groups of CoCrFeNi: NiAl: Nb are 70% to 87%: 10% to 24%: 3% to 9% respectively. The preparation process is as follows: select raw materials with a purity higher than 99.95wt%, first use a non-consumable vacuum arc melting furnace to melt the CoCrFeNi, NiAl and Nb raw materials, and finally obtain a three-phase eutectic high-entropy alloy. The three-phase eutectic high-entropy alloy described in the present invention has better comprehensive mechanical properties than traditional high-entropy alloys. The eutectic high-entropy alloy has good strength-plasticity matching and broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of traditional eutectic high entropy alloys and preparation thereof, and provides a high-strength and toughness three-phase eutectic high entropy alloy and a preparation method thereof. Background Art

[0002] For a long time, the design ideas of traditional alloys are usually based on one or two elements, and other trace elements are added to optimize their mechanical, physical and chemical properties. For example, steel materials, aluminum alloys, copper alloys, titanium alloys, etc. are widely used in engineering technology, automobiles, aerospace, machinery manufacturing and other fields. In the 21st century, Professor Ye Junwei of National Tsing Hua University in Taiwan and Professor Cantor of the United Kingdom proposed a new alloy, namely multi-principal alloy or high entropy alloy. This concept has attracted widespread attention as soon as it was proposed. Compared with traditional alloys, high entropy alloys have four major effects: high entropy effect, lattice distortion effect, hysteresis diffusion effect and cocktail effect. These effects make high entropy alloys have more unique properties, such as extraordinary damage tolerance and fracture toughness at liquid nitrogen temperature, ultra-high strength at room temperature and excellent corrosion resistance, etc. These properties make such alloys show great application prospects.

[0003] In 2014, Professor Lu Yiping designed the AlCoCrFeNi with (FCC + B2) phase structure. 2.1 Alloy, and for the first time proposed the concept of eutectic high entropy alloy. The characteristics of this alloy with low melting point and no solid-liquid mixed zone fundamentally solve the problems of poor casting fluidity and component segregation of high entropy alloy.

[0004] So far, eutectic high entropy alloys have been continuously developed and studied by researchers. As we all know, CoCrFeNi high entropy alloys are single FCC structures, and the single-phase FCC structure exhibits excellent plasticity but poor strength. In order to improve the comprehensive properties of the alloy, this effect is achieved by introducing NiAl alloys and Nb elements that easily produce Laves phases. Summary of the invention

[0005] In order to improve the strength-plasticity matching of eutectic high entropy alloys, the present invention provides a high-strength and toughness three-phase eutectic high entropy alloy and a preparation method thereof, wherein the alloy can exhibit excellent mechanical properties.

[0006] In order to achieve the purpose of the present invention, the following technical solutions are provided:

[0007] A high-strength and tough three-phase eutectic high-entropy alloy and a preparation method thereof, wherein the atomic percentages of the three components of CoCrFeNi: NiAl: Nb are 70%-87%: 10%-24%: 3%-9%, respectively.

[0008] The preparation method comprises the following steps:

[0009] Step 1, selecting Co, Cr, Fe, Ni, Nb and NiAl alloys with purity higher than 99.95wt.% as raw materials;

[0010] Step 2: remove the surface oxide scale of metal Co, Cr, Fe, Ni, Nb and NiAl alloy, clean and dry.

[0011] Step 3: The raw materials obtained in step 2 are placed in a smelting furnace and heated to a vacuum of 9.5×10 -3 The smelting was carried out under Pa. CoCrFeNi-Nb, CoCrFeNi-NiAl eutectic high entropy alloys and NiAl-Nb eutectic alloys were obtained respectively after smelting, and finally a three-phase eutectic high entropy alloy was obtained by smelting.

[0012] Specific smelting operation: first, place Co, Cr, Fe and Ni on the bottom layer of the leftmost crucible, and then place Nb on the upper layer; similarly, place NiAl alloy on the bottom layer of the middle crucible, and then place Co, Cr, Fe and Ni raw materials on the upper layer; similarly, place NiAl alloy on the bottom layer of the rightmost crucible, and then place Nb raw materials on the upper layer. Vacuum to 9.5×10 -1 Pa, and then filled with high-purity argon gas (purity 99.99%) to -0.5×10 5 Mpa, the purpose is to exhaust the residual oxygen in the furnace. Vacuum again and use a molecular pump to pump the pressure in the furnace to 9.5×10 -3 Pa, and then filled with argon to -0.5×10 5 MPa. Move the electrode downward, keep the distance between the electrode and the crucible containing pure Ti at about 3-6mm, control the current to about 20A for arc melting, and keep this operation for 2-3 minutes to remove residual oxygen in the furnace. Then move the tungsten rod to the crucible containing the raw materials, control the current to 15-20A for arc melting, slowly increase the current to 350A, keep this operation for 7-10 minutes to fully melt the metal, close the electrode and wait for cooling to form a metal ingot. Move the electrode, align the electrode with the materials in the middle and leftmost crucibles in turn and repeat the above melting operation. When the melting of the middle crucible is completed, close the electrode and use the robotic arm to turn over the metal ingot in the leftmost crucible. Similarly, after each metal ingot is melted, use the robotic arm to turn over the previous cooled metal ingot, repeat the melting and turning operation 6 times to obtain CoCrFeNi-Nb, CoCrFeNi-NiAl eutectic high entropy alloys and NiAl-Nb eutectic alloys.

[0013] The three eutectic high entropy alloys obtained above are placed in the same crucible using a robotic arm, and the above steps are repeated for smelting to finally obtain a three-phase eutectic high entropy alloy.

[0014] Regarding the preferred solution for smelting, after the raw materials are placed in the smelting furnace, the vacuum is evacuated to 9.5×10 -1 Pa, filled with argon to -0.5×10 5 MPa, and then use a molecular pump to evacuate the furnace to 9.5×10 -3 Pa, and then filled with argon to -0.5×10 5 MPa. When the arc moves to the crucible with raw materials, first set the current intensity to 10-30A for arc initiation, then slowly increase the current to 50-60A, smelt for 30-60s, continue to increase the current to 120-150A, smelt for 2-3min, increase the current to 300-320A again, smelt for 2-3min, and finally increase the current to 350A for 2-3min.

[0015] The technical concept of the present invention is: CoCrFeNi alloy has a stable FCC phase structure, which has good plasticity but poor strength. The mechanical properties of the alloy can be effectively improved by adding NiAl alloy and Nb element.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The invention effectively adjusts the microstructure of the alloy by reasonably adjusting the composition ratio of CoCrFeNi: NiAl: Nb; and adopts different smelting methods and raw material laying sequences to improve the comprehensive performance of the alloy.

[0018] The present invention provides a three-phase eutectic high entropy alloy. The three-phase eutectic high entropy alloy phases are composed of FCC + Laves + NiAl, and the eutectic high entropy alloy has good strength-plasticity matching and broad application prospects.

[0019] Within the composition range and process of the present invention, a multi-scale and multi-level structure of the microstructure can be achieved, and the three-phase eutectic is easier to form a smaller interlaminar spacing than the two-phase eutectic, thereby achieving fine grain strengthening. The advantage of this process is that the alloy ingots formed by smelting in any three crucibles are all two-phase eutectic alloys, which can be smelted at a lower current to reduce the evaporation of the aluminum element. If all are mixed in one crucible for smelting, firstly, the alloy ingot has a large mass and requires a large current, which increases the evaporation of the aluminum element. Secondly, the composition is easily uneven during the subsequent solidification process, and the formation of a three-phase eutectic structure at a low aluminum content cannot be guaranteed. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the XRD pattern of the cast three-phase eutectic high entropy alloy.

[0021] Figure 2 (NiAl) obtained in Example 1 17 (CoCrFeNi)74 Metallographic diagram of cast Nb three-phase eutectic high entropy alloy.

[0022] Figure 3 (NiAl) obtained in Example 2 24 (CoCrFeNi) 70 Metallographic image of Nb6 three-phase eutectic high entropy alloy as cast.

[0023] Figure 4 (NiAl) obtained in Example 3 20 (CoCrFeNi) 72 Metallographic diagram of cast Nb8 three-phase eutectic high entropy alloy.

[0024] Figure 5 This is the room temperature compression engineering stress-strain curve of the cast three-phase eutectic high entropy alloy. DETAILED DESCRIPTION

[0025] The microstructure characterization and mechanical properties test information of the prepared three-phase eutectic high entropy alloy are as follows:

[0026] Phase analysis: X-ray diffraction analysis was performed using an Ultima IV Cu Kα diffractometer (λ=1.54Å), with an operating voltage and current of 40KV and 40mA, respectively, with a 2θ scanning range from 20° to 100° and a speed of 4 / min. The results are shown in Figure 1 .

[0027] Microstructure: The morphology of the sample was observed under different magnifications using a scanning electron microscope. Figure 2-4 .

[0028] Mechanical properties: According to the relevant requirements of GB / T 7314-2017 Metal Material Room Temperature Compression Test Method, a room temperature compression test was carried out with a compression loading rate of 0.36 mm / min. Three compression tests were carried out on alloys with different compositions, and the stress-strain curve data were averaged three times. The results are as follows: Figure 5 .

[0029] The invention will be further explained below with reference to specific implementation cases.

[0030] Example 1

[0031] This case discloses the preparation of a (NiAl) 17 (CoCrFeNi) 74 Nb9 three-phase eutectic high entropy alloy.

[0032] Step 1: Select six elements, namely Co, Cr, Fe, Ni, Nb and NiAl alloy, as raw materials, and the purity of all metal raw materials is greater than 99.95wt.%;

[0033] Step 2: First, according to the total alloy ingot mass of 45g, divide it into three small metal ingots of different masses. After mass percentage conversion, the weighed weights of raw material 1: Co, Cr, Fe, Ni and Nb are 4.62g, 4.08g, 4.38g, 4.6g and 3.28g respectively;

[0034] Raw material 2: The weighed masses of Co, Cr, Fe, Ni and NiAl alloy are 3.93 g, 3.47 g, 3.73 g, 3.91 g and 2.86 g respectively;

[0035] Raw material 3: The weighing masses of NiAl alloy and Nb are 2.86 g and 3.28 g respectively, and the weighing error of all raw materials is ±0.001 g.

[0036] Step 3: Use different types of SiC sandpaper (240#, 400#, 800# and 1200#) to polish the surface of the raw material to remove impurities and oxide layer on the metal surface, then wash with anhydrous ethanol, dry, bag and seal for later use;

[0037] Step 4: First, put the raw materials into three crucibles of the melting furnace respectively, and use the moving electrode to melt to obtain CoCrFeNi-Nb, CoCrFeNi-NiAl eutectic high entropy alloy and NiAl-Nb eutectic alloy; then use the robotic arm to put the three alloys into the same crucible, and continue to melt to obtain the three-phase eutectic high entropy alloy.

[0038] The specific operation is as follows: after the mass percentage conversion of small metal ingots of different masses, the weighed weights of raw material 1: Co, Cr, Fe, Ni and Nb are 4.62g, 4.08g, 4.38g, 4.6g and 3.28g respectively; raw material 2: the weighed weights of Co, Cr, Fe, Ni and NiAl are 3.93g, 3.47g, 3.73g, 3.91g and 2.86g respectively; raw material 3: the weighed masses of NiAl and Nb are 2.86g and 3.28g respectively, and the weighing error of all raw materials is ±0.001g.

[0039] First, put the raw materials into the melting furnace according to their melting points (Co, Cr, Fe and Ni are placed on the bottom of the first crucible, and then the raw material Nb is placed on the upper layer. Similarly, NiAl alloy is placed on the bottom of the second crucible, and then Co, Cr, Fe and Ni raw materials are placed on the upper layer. Similarly, NiAl alloy is placed on the bottom of the third crucible, and then the raw material Nb is placed on the upper layer. The purpose is to allow the raw materials to be fully melted in the crucible). After the raw materials are placed, close the furnace door and evacuate to 9.5×10 -1 Pa, and then introduce 99.99% pure argon gas to -0.5×10 5 Mpa. Evacuate the furnace again and use a molecular pump to reduce the pressure in the furnace to -0.5×105 Mpa, and then introduce argon to -0.5×10 5 MPa. Move the electrode downward, keep the distance between the electrode and the crucible containing pure Ti at about 3-6mm, control the current to about 20A to start arc melting, and keep this operation for 2-3min to remove residual oxygen in the furnace. Then move the electrode to the first crucible containing raw materials, shake the electrode slightly so that the molten metal completely penetrates into the second layer, and increase the current to 350A for melting. Keep this operation for 7-10min to make the metal fully melted, close the electrode and wait for cooling to form a metal ingot. Next, move the electrode to the second crucible, and slowly lower it to align it with the upper layer of Co, Cr, Fe and Ni raw materials. When the metal begins to melt, shake the electrode slightly so that the molten metal completely penetrates into the second layer of NiAl alloy, and increase the current to 350A while moving the electrode downward. Keep this operation for 7-10min to make the molten metal flow fully, close the electrode and wait for cooling to form the second metal ingot. When the second crucible is melted, use the robotic arm to turn over the metal ingot in the first crucible. Continue to move the electrode, align the electrode with the raw materials in the third crucible, shake the electrode to melt the Nb metal first, and allow the molten metal to fully penetrate into the NiAl alloy. Continue to move the electrode down for 7-10 minutes, close the electrode and wait for cooling to form the third metal ingot. At this time, use the robotic arm to turn over the metal ingot in the third crucible, and so on. Repeat the above operation 6 times to finally obtain CoCrFeNi-Nb, CoCrFeNi-NiAl eutectic high entropy alloy and NiAl-Nb eutectic alloy.

[0040] Step 5: Use a robotic arm to place the three alloys obtained in step 4 into the same crucible, and then continue to evacuate and smelt (repeat the operation of step 4) to obtain (NiAl) 17 (CoCrFeNi) 74 Nb9 three-phase eutectic high entropy alloy.

[0041] In the embodiment (NiAl) 17 (CoCrFeNi) 74 The Nb9 three-phase eutectic high entropy alloy sample was subjected to phase analysis, and its X-ray diffraction (XRD) spectrum is shown in Figure 1 As shown in the figure, it can be seen that the alloy has a three-phase structure of FCC + Laves + NiAl.

[0042] For this example (NiAl) 17 (CoCrFeNi) 74 The microstructure of the Nb9 three-phase eutectic high entropy alloy sample was analyzed, and the scanning electron microscope (SEM) photos are shown in Figure 2From the analysis of the figure, we can see that the alloy first precipitates a large piece of FCC phase (gray phase), and a layer of Laves phase is basically wrapped around the FCC phase. Small pieces of FCC and Laves phase form a two-phase eutectic, and the three-phase eutectic area is a layered structure (FCC + Laves + NiAl).

[0043] For this example (NiAl) 17 (CoCrFeNi) 74 The Nb9 three-phase eutectic high entropy alloy sample was subjected to room temperature compression test, and its compression true stress-strain curve is shown in Figure 5 As shown, it can be seen that (NiAl) 17 (CoCrFeNi) 74 The yield strength of Nb9 alloy is 1049.7MPa, the compressive strength is 2040MPa, and the fracture strain is 22.5%.

[0044] Example 2

[0045] This case discloses a (NiAl) 24 (CoCrFeNi) 70 Nb6 three-phase eutectic high entropy alloy.

[0046] Step 1: Select six elements, namely Co, Cr, Fe, Ni, Nb and NiAl alloy, as raw materials, and the purity of all metal raw materials is greater than 99.95wt.%.

[0047] Step 2: First, according to the total alloy ingot mass of 45g, divide it into three small metal ingots of different masses. After mass percentage conversion, the weighed weights of raw material 1: Co, Cr, Fe, Ni and Nb are 4.47g, 3.95g, 4.24g, 4.46g and 4.23g respectively;

[0048] Raw material 2: The weighed masses of Co, Cr, Fe, Ni and NiAl alloy are 3.36 g, 2.96 g, 3.18 g, 3.34 g and 3.28 g respectively;

[0049] Raw material 3: The weighing masses of NiAl alloy and Nb are 3.28 g and 4.23 g respectively, and the weighing error of all raw materials is ±0.001 g.

[0050] The preparation scheme of the three-phase eutectic high entropy alloy in this case is the same as that in Case 1.

[0051] In the embodiment (NiAl) 24 (CoCrFeNi) 70 The Nb6 three-phase eutectic high entropy alloy sample was subjected to phase analysis, and its X-ray diffraction (XRD) spectrum was as follows Figure 1As shown in the figure, it can be seen that the alloy also has FCC + NiAl + Laves structure.

[0052] For this example (NiAl) 24 (CoCrFeNi) 70 The microstructure of the Nb6 three-phase eutectic high entropy alloy sample was analyzed, and the scanning electron microscope (SEM) photos are shown in Figure 3 From the analysis of the figure, we can see that the alloy first precipitates a large piece of FCC phase (gray phase), and many small pieces of black NiAl phase will precipitate around the FCC phase, and the three-phase eutectic area is a layered structure (FCC + Laves + NiAl).

[0053] For this example (NiAl) 24 (CoCrFeNi) 70 The Nb6 three-phase eutectic high entropy alloy sample was subjected to room temperature compression test, and its compression true stress-strain curve is shown in Figure 5 As shown, it can be seen that (NiAl) 24 (CoCrFeNi) 70 The yield strength of Nb6 alloy is 1027.4MPa, the compressive strength is 2127.7MPa, and the fracture strain is 27.9%.

[0054] Example 3

[0055] This case discloses a (NiAl) 20 (CoCrFeNi) 72 Nb8 three-phase eutectic high entropy alloy.

[0056] Step 1: Select six elements, namely Co, Cr, Fe, Ni, Nb and NiAl alloy, as raw materials, and the purity of all metal raw materials is greater than 99.95wt.%.

[0057] Step 2: First, according to the total alloy ingot mass of 45g, divide it into three small metal ingots of different masses. After mass percentage conversion, the weighed weights of raw material 1: Co, Cr, Fe, Ni and Nb are 4.58g, 4.04g, 4.34, 4.56g and 3.61g respectively;

[0058] Raw material 2: The weighed masses of Co, Cr, Fe, Ni and NiAl alloy are 3.67 g, 3.23 g, 3.47 g, 5.67 g and 2.11 g respectively;

[0059] Raw material 3: The weighing masses of NiAl alloy and Nb are 2.11 g and 3.61 g respectively, and the weighing error of all raw materials is ±0.001 g.

[0060] The preparation scheme of the three-phase eutectic high entropy alloy in this case is the same as that in Case 1.

[0061] In the embodiment (NiAl) 20 (CoCrFeNi) 72 The Nb8 three-phase eutectic high entropy alloy sample was subjected to phase analysis, and its X-ray diffraction (XRD) spectrum is shown in Figure 1 As shown in the figure, it can be seen that the alloy also has a FCC + NiAl + Laves structure.

[0062] For this example (NiAl) 20 (CoCrFeNi) 72 The microstructure of the Nb8 three-phase eutectic high entropy alloy sample was analyzed, and the scanning electron microscope (SEM) photos are shown in Figure 4 ,From the analysis of the figure, it can be seen that the alloy first precipitates a large piece of FCC phase (gray phase), and then directly forms a three-phase eutectic, and the three-phase eutectic area is a layered structure (FCC + Laves + NiAl).

[0063] For this example (NiAl) 20 (CoCrFeNi) 72 The Nb8 three-phase eutectic high entropy alloy sample was subjected to room temperature compression test, and its compression true stress-strain curve is shown in Figure 5 As shown, it can be seen that (NiAl) 20 (CoCrFeNi) 72 The yield strength of the Nb alloy is 1077.4MPa, the compressive strength is 2129.4MPa, and the fracture strain is 25.2%.

[0064] The above implementation cases are only for illustrating the design scheme of the invention, but not for limiting it. Those skilled in the art can still improve the above design scheme, and these improved schemes still do not deviate from the scope of the technical methods of the implementation cases of the present invention.

Claims

1. A high-strength and high-toughness three-phase eutectic high-entropy alloy, characterized in that: The three-phase eutectic high entropy alloy is a three-phase eutectic high entropy alloy having a structure of FCC+Laves+NiAl formed by mixed melting of CoCrFeNi:NiAl:Nb in molar percentages of 70%-87%:10%-24%:3%-9%. Mixed smelting includes the following steps: (1) Co, Cr, Fe, Ni, Nb and NiAl alloy are selected as raw materials for batching; (2) Placing the raw materials of CoCrFeNi-Nb eutectic high entropy alloy: Place the raw materials of Co, Cr, Fe, Ni and Nb in the first crucible; (3) Placing the CoCrFeNi-NiAl eutectic high entropy alloy raw materials: Placing the NiAl alloy, Co, Cr, Fe and Ni raw materials in the second crucible; (4) Placing NiAl-Nb eutectic alloy raw materials: Place NiAl alloy and Nb raw materials in the third crucible; (5) placing the first crucible, the second crucible, and the third crucible in a smelting furnace respectively, evacuating the furnace, and using electrodes to melt the raw materials in the first crucible, the second crucible, and the third crucible in turn. After the raw materials are melted evenly, the electrodes are closed and cooled to obtain CoCrFeNi-Nb eutectic high entropy alloy, CoCrFeNi-NiAl eutectic high entropy alloy, and NiAl-Nb eutectic alloy respectively; (6) The CoCrFeNi-Nb eutectic high entropy alloy, the CoCrFeNi-NiAl eutectic high entropy alloy and the NiAl-Nb eutectic alloy are placed in the same crucible and smelted to obtain a three-phase eutectic high entropy alloy.

2. The high-strength and tough three-phase eutectic high-entropy alloy according to claim 1, characterized in that: The raw materials of the three-phase eutectic high entropy alloy include CoCrFeNi:NiAl:Nb in molar percentages of 70%~74%:17%~24%:6%~9%.

3. The method for preparing a high-strength and tough three-phase eutectic high-entropy alloy according to claim 1 or 2, characterized in that: The steps include: (1) Co, Cr, Fe, Ni, Nb and NiAl alloys are selected as raw materials for batching; (2) Placing the raw materials of CoCrFeNi-Nb eutectic high entropy alloy: Place the raw materials of Co, Cr, Fe, Ni and Nb in the first crucible; (3) Placing the CoCrFeNi-NiAl eutectic high entropy alloy raw materials: Placing the NiAl alloy, Co, Cr, Fe and Ni raw materials in the second crucible; (4) Placing NiAl-Nb eutectic alloy raw materials: Place NiAl alloy and Nb raw materials in the third crucible; (5) placing the first crucible, the second crucible, and the third crucible in a smelting furnace respectively, evacuating the furnace, and using electrodes to melt the raw materials in the first crucible, the second crucible, and the third crucible in turn. After the raw materials are melted evenly, the electrodes are closed and cooled to obtain CoCrFeNi-Nb eutectic high entropy alloy, CoCrFeNi-NiAl eutectic high entropy alloy, and NiAl-Nb eutectic alloy respectively; (6) The CoCrFeNi-Nb eutectic high entropy alloy, the CoCrFeNi-NiAl eutectic high entropy alloy and the NiAl-Nb eutectic alloy are placed in the same crucible and smelted to obtain a three-phase eutectic high entropy alloy.

4. The method for preparing a high-strength and tough three-phase eutectic high-entropy alloy according to claim 3, characterized in that: In step (2), the CoCrFeNi-Nb eutectic high entropy alloy raw materials are placed: Co, Cr, Fe and Ni raw materials are placed on the bottom layer of the first crucible of the smelting furnace, and then the raw material Nb is placed on the upper layer; In step (3), the CoCrFeNi-NiAl eutectic high entropy alloy raw materials are placed: the NiAl alloy is placed on the bottom layer of the second crucible, and then the Co, Cr, Fe and Ni raw materials are placed on the upper layer; In step (4), the NiAl-Nb eutectic alloy raw materials are placed: the NiAl alloy is spread on the bottom layer of the third crucible, and then the Nb raw material is spread on the upper layer.

5. The method for preparing a high-strength and tough three-phase eutectic high-entropy alloy according to claim 4, characterized in that: The upper layers of the raw materials in the first crucible, the second crucible, and the third crucible are melted respectively, and then the lower layers are melted, while shaking the electrodes to allow the molten metal to flow fully, and the melting is performed for 7-10 minutes.

6. The method for preparing a high-strength and tough three-phase eutectic high-entropy alloy according to claim 5, characterized in that: The CoCrFeNi-Nb eutectic high entropy alloy, the CoCrFeNi-NiAl eutectic high entropy alloy and the NiAl-Nb eutectic alloy are placed in the same crucible and melted for 7-10 min.

7. The method for preparing a high-strength and tough three-phase eutectic high-entropy alloy according to claim 6, characterized in that: When the arc moves to the crucible containing raw materials, first set the current intensity to 10-30A, then slowly increase the current to 50-60A, melt for 30-60s, continue to increase the current to 120-150A, melt for 2-3min, increase the current to 300-320A again, melt for 2-3min, and finally increase the current to 350A and melt for 2-3min.

8. The method for preparing a high-strength and tough three-phase eutectic high-entropy alloy according to any one of claims 3 to 7, characterized in that: A high-strength and tough three-phase eutectic high-entropy alloy was prepared by this method.